Bacterial and antimicrobial resistance profile of bloodstream infections: A hospital-based study - Amit Kumar Singh; Vimala Venkatesh; Ravinder Pal Singh; Mastan Singh (Wolters Kluwer Medknow Publications, 2014)
Background: Bloodstream infections (BSIs) are one of the serious infections causing significant morbidity and mortality among hospitalized patients. Large numbers of cases of treatment failure are being reported due to emergence of drug resistance. Early microbiological diagnosis and determination of antimicrobial susceptibility pattern have been shown to improve treatment outcome. The present study was aimed to determine the bacterial and antimicrobial resistance profile of BSIs in a major tertiary care hospital. Materials and Methods: Blood samples in brain heart infusion (BHI) broth submitted to the microbiology laboratory for culture and sensitivity during a period of 1 year were included in the study. Samples were processed as per standard protocol of laboratory for isolation and identification. The antimicrobial susceptibility profile of bacterial isolates was determined by the disc diffusion method as per Clinical and Laboratory Standards Institute (CLSI) guidelines. Results: Out of 4862 blood samples, 494 (10.16%) isolates were obtained. Of these isolates, 256 (51.82%) were Gram-negative and 230 (46.56%) were Gram-positive bacteria. The most commonly identified organism was coagulase-negative Staphylococcus (CoNS) (25.91%) followed by Acinetobacter spp. (20.24%) and Escherichia coli (14.98%). Gram-negative bacteria showed a higher rate of resistance as compared with Gram-positive bacteria. Conclusion: High prevalence of antimicrobial resistance was noted in this study, especially in Gram-negative bacteria. Hence, appropriate treatment of BSIs should be based on the current knowledge of bacterial resistance profile as provided by microbiology laboratory. It would be advisable for the clinicians to mandate antimicrobial sensitivity testing for suspected cases of BSIs.